Unsafe Care and Fake News in Freeman–Burian Syndrome - Mikaela I. Poling; Craig R. Dufresne (Clinical Case Reports)
ABSTRACT Freeman‐Burian syndrome is a rare craniofacial syndrome surrounded by fake news. This situation shows the strong connection between the quality of a literature search and clinical reasoning displayed in patient care, especially in care of patients with rare conditions.